Penyediaan Tempat Istirahat Pada Jalan Umum Melalui Corporate Social Responsibiliy - Hendra Hendrawan (Politeknik Negeri Jakarta, 2020)
Rest Areas on non toll roads are road equipment that are not directly related to road users whose primary function is to reduce the number of accidents caused by driver and vehicle fatigue. This is in accordance with the agenda of the National General Plan of Road Safety (RUNK) to provide preventive infrastructure against potential accidents. To provide safe, convenient, secure, and sustainable rest areas, the government is faced with funding constraints. In the implementation, the construction of rest areas require funds that are not little, especially for land procurement and physical infrastructure development. For that reason, funding alternative is needed through Corporate Social Responsibility. This paper aimed to examine the feasibility of rest areas development through Corporate Social Responsibility by considering the aspect of legality and potential problems. The method used was literature review which included the aspects of feasibility, legality, and mechanism. The results showed that the rest areas can be part of Corporate Social Responsibility. The results of the study also indicated the need for additional tools in the form of regulations and guidelines to govern the partnership pattern so that development through this mechanism is well-running, supervised, and accountable